The configuration of the procurement area and the job of the procurer in car assemblies: new tasks and profile - Lima, José Carlos de Souza; Marx, Roberto (Revista Gestão da Produção Operações e Sistemas, 2008)
This article studies the work of the buyer in the automobile industry analyzing his professional profile as well ashis skills since the decade of 90 in two assemblers located at the so called ABC Paulista. It considers that the newsupply relationships, the application of just in time/kanban and lean production, the intensification of Internetand EDI (Electronic Data interchange) in transactions involved in the supply chain and the internationalizationof the automotive sector have all increased the importance of the purchasing area and have modified therole that the buyer play inducing him to act more proactively in the conduction of the relationship between thesupplier and the assembler firms.Keywords: purchase; competence; structures of purchases; ethics.